The Impact of Impulse Buying Behavior and Hedonistic Lifestyle of IAIN Manado Students on Sharia Investment: An Islamic Economic Perspective - Gafur, Mardatilla Kartika; Bukido, Rosdalina; Jamal, Ridwan (Kunuz: Journal of Islamic Banking and Finance, 2024)
This study aims to analyze the impact of IAIN Manado students' impulse buying behavior and hedonistic lifestyles on Shariah investment from an Islamic economics perspective. Impulse buying behavior, characterized by spontaneous purchases without rational consideration and a hedonistic lifestyle focused on material satisfaction and pleasure, is increasingly prevalent among students. This phenomenon can affect the allocation of funds that should be invested in Shariah-compliant instruments by Islamic economic principles. This study employs a qualitative approach using case study methods and in-depth interviews with students from the Faculty of Islamic Economics and Business at IAIN Manado. The results indicate that impulsive behavior and a hedonistic lifestyle tend to reduce students' awareness and interest in Sharia-compliant investments. This is due to priorities shifting from productive long-term investments to unplanned short-term consumption. From an Islamic economics perspective, such behavior contradicts the principles of prudent and responsible financial management. The study recommends enhancing Shariah's financial literacy and promoting awareness about the importance of Shariah-compliant investments to foster sustainable well-being.